Analytical investigation of gas production from methane hydrates and the associated heat and mass transfer upon thermal stimulation employing a coaxial wellbore. (1st April 2020) - Roostaie, M.; Leonenko, Y.
Highlights: Methane production is strongly dependent on heat-source geometry and composition. Well temperature affects both the pressure and temperature at the dissociation front. Raising temperature and decreasing pressure of the well increases gas production. Abstract: In this study, an analytical approach has been developed to couple the wellbore heating process by hot water circulation and the associated methane hydrate dissociation in the reservoir. A coaxial wellbore is assumed as the heat source where both conduction and convection heat transfers are considered. It consists of an inner tube and an outer structure of casing, gravel, and cement layers. In the reservoir, a similarity solution employing a moving boundary separating the dissociated and undissociated zones is employed to build the analytical solution. Two different operating schemes for water supply into wellbore heat source have been studied: i) from the inner tube; and ii) from the annulus section of the wellbore. Temperature distribution along the wellbore, temperature and pressure distributions in the reservoir, hydrate dissociation rate, and energy efficiency considering various initial and boundary conditions and reservoir properties are evaluated. The two different operating schemes have almost the same results with slightly higher gas production in the case of hot water entry into annulus, which is in direct contact with the reservoir. Increasing the inlet water temperature or decreasing the wellbore pressure increases gas production. Applying them simultaneously results in a greater gas production and energy efficiency. Some of the reservoir's properties, such as porosity, thermal diffusivity, thermal conductivity, and reservoir thickness, have direct relation with the dissociation rate, but the reservoir's permeability and gas viscosity have almost no impact on the process. The wellbore parameters, such as flow rate of hot water, inlet temperature, and wellbore radius except the inner tube radius, have direct impact on the wellbore mean temperature and the associated results in the dissociation process.